Manifesta 4 : Europäische Biennale Zeitgenössischer Kunst. - Manifesta Frankfurt/Main 2002; Boubnova, Iara; Mayo, Nuria Enguita; Trembley, Stéphanie Moisdon; Fritz, Martin; Volz, Jochen; Müller, Vanessa Joan; Troncy, Eric (Ostfildern-Ruit : Hatje Cantz, 2002)
Altindere, Halil ; Andújar, Daniel Garcia ; APSOLUTINO ; Aranberri, Ibon ; Bardin, Olivier ; Bartana, Yael ; Bartolini, Massimo ; Bijl, Mar ; Bismuth, Pierre ; Bleda y Rosa ; BLESS ; Boyadjiev, Luchezar ; van den Brink, Jasper ; et al.
Frankfurt/Main, 25 May to 25 August 2002
kunstcatalogus